The great radio sitcoms - Cox, Jim 1939- (McFarland, 2007)
"This volume examines 20 of the most popular sitcoms which aired between the mid-1920s and early 1950s during the three decade heyday of radio. Each series is discussed from an artistic standpoint, taking a look at the program's character development and extent of vaudeville heritage"--Provided by publisher
Includes bibliographical references (p. 279-281) and index
Keywords: Geschichte 1928-1955; Radio comedies / United States / History and criticism; Radio comedies -- United States -- History and criticism; Situationskomödie; Hörfunksendung; USA